(3agQSJ CMeO GdefLhQs - (3CMeO Hf Ydj Hf YHO GdQMef GdefLhQ,J (B995 (3g` s
(3ChdgG (B:s
(3deG JCbJ Gdgee GdYdjI hGdfaS GdcQjeI GdefUhQjI s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B10s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(5164) s
Keywords: (3GdJGQjNs